1987
DOI: 10.1002/chin.198719082
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Enantioselective C‐C Bond Formation with Chiral Lewis Acids.

Abstract: The preparation of chiral Lewis acids (I) ‐ (III) which have bidentate ligands is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 0 publications
0
33
0
3
Order By: Relevance
“…Of particular interest are those complexes derived from an enantiomerically pure chelating diol. Thus, [TiCl 2 (BINOLato)] complexes (BINOLato [1,1'-binaphthalene]-2,2'-diolato(2 À)-kO,kO') have found specific use in enantioselective Mukaiyama aldol reactions [2], cyanosilylation of aldehydes [2], carbonyl-ene reactions [3], carbonyl allylsilane or allylstannane additions [4 ± 6], ene cyclizations [7], (hetero)-Diels-Alder reactions [8], and others (for a review, see [9]). Complexes of the type [TiCl 2 (TADDOLato)] 1 ) serve as catalysts in enantioselective cyanosilylations [10], (hetero)-Diels-Alder [11 ± 15], [2 2] cycloadditions [16 ± 18], [2 3] cycloadditions [19], 1,3-dipolar cycloadditions [20], nitro-aldol reactions [21], fluorinations [22], and others (for reviews, see [9] [23]).…”
mentioning
confidence: 99%
“…Of particular interest are those complexes derived from an enantiomerically pure chelating diol. Thus, [TiCl 2 (BINOLato)] complexes (BINOLato [1,1'-binaphthalene]-2,2'-diolato(2 À)-kO,kO') have found specific use in enantioselective Mukaiyama aldol reactions [2], cyanosilylation of aldehydes [2], carbonyl-ene reactions [3], carbonyl allylsilane or allylstannane additions [4 ± 6], ene cyclizations [7], (hetero)-Diels-Alder reactions [8], and others (for a review, see [9]). Complexes of the type [TiCl 2 (TADDOLato)] 1 ) serve as catalysts in enantioselective cyanosilylations [10], (hetero)-Diels-Alder [11 ± 15], [2 2] cycloadditions [16 ± 18], [2 3] cycloadditions [19], 1,3-dipolar cycloadditions [20], nitro-aldol reactions [21], fluorinations [22], and others (for reviews, see [9] [23]).…”
mentioning
confidence: 99%
“…This catalyst resulted in moderate induction with several aldehydes including the three shown in Sch. 6 Asymmetric induction was found not to be dependent on catalyst loading. For example, addition to cyclohexane carboxaldehyde occurred with 56 YO ee whether 100 or 10 mol YO catalyst was used, although the reaction was slower for the latter, proceeding in 17 h rather than 0.5 h. Several other ligands were evaluated for this reaction and it was found that ligand 48, derived from the cyclohexyl amide of valine was optimal in terms of rate and asymmetric induction.…”
Section: Carbonyl Additions and Reductionsmentioning
confidence: 97%
“…The earliest such carbonyl addition reaction to be reported was, along with the Muikaiyama aldol reaction of ketene acetal7 (Sch. 2), the addition of trimethylsilyl cyanide to iso-valeraldehyde [6]. The catalyst 13 did not result in asymmetric induction as high in this reaction as it did with the Muikaiyama aldol reaction of ketene acetal 7 with iso-valeraldehyde (Sch.…”
Section: Carbonyl Additions and Reductionsmentioning
confidence: 99%
“…Catalytic asymmetric aldol reaction involving ligands possessing symmetry elements of pure rotation such as BINOL and derivatives have been extensively studied. Reetz et al 36 firstly reported enantioselective Mukaiyama aldol reactions involving BINOL-Ti(IV) complex as Lewis acid.…”
Section: Binol and Related Ligands In Catalytic Stereoselective Mukaimentioning
confidence: 99%